Effect of an aerodynamic helmet on head temperature, core temperature, and cycling power compared with a traditional helmet - Lee, J. F.; Brown, S. R.; Lange, A. P.; Brothers, R. M. (The Journal of Strength and Conditioning Research, 2013)
Nonvented "aerodynamic helmets" reduce wind resistance but may increase head (Th) and gastrointestinal (Tgi) temperature and reduce performance when worn in hot conditions. This study tested the hypothesis that Th and Tgi would be greater during low-intensity cycling (LIC) in the heat while wearing an aero helmet (AERO) vs. a traditional vented racing helmet (REG). This study also tested the hypothesis that Th, Tgi, and finish time would be greater, and power output would be reduced during a self-paced time trial in the heat with AERO vs. REG. Ten highly trained heat-acclimated endurance athletes conducted LIC (50% VO2max, LIC) and a high-intensity 12-km self-paced time trial (12-km TT) on a cycle ergometer in 39° C on 2 different days (AERO and REG), separated by >48 hours. During LIC, Th was higher at minute 7.5 and all time points thereafter in AERO vs. REG (p < 0.05). Similarly, during the 12-km TT, Th was higher at minutes 12.5, 15, and 17.5 in AERO vs. REG (p < 0.05). Heart rate (HR) and Tgi increased during LIC and during 12-km TT (both p < 0.001); however, no significant interaction (helmet × time) existed for HR or Tgi at either intensity (all p > 0.05). No group differences existed for finish time or power output during the 12-km TT (both p > 0.05). In conclusion, Th becomes elevated during cycling in the heat with an aero helmet compared with a traditional vented racing helmet during LIC and high-intensity cycling, yet Tgi and HR responses are similar irrespective of helmet type and Th. Furthermore, the higher Th that develops when an aero helmet is worn during cycling in the heat does not affect power output or cycling performance during short-duration high-intensity events.